The Moderating Effect of Leadership Style in Relation between Workplace Innovation on Employee Performance - Piriyawatthana, Wallop (International Journal of Psychosocial Rehabilitation, 2020)
Purpose The purpose of this research is related to determining the moderating effect of leadership style affecting the relationship between workplace innovation and employee performance.Design/ Method/ ApproachThe study has been formed on the basis of the quantitative analysis by means of SEM as a statistical technique. The study concerned with determining the moderating effect for which the SmartPLS has been preferred to analyse the survey questionnaire collected from 369 employees working for different organisations operating in Malaysia.FindingsThe findings of this study suggest that leadership style significantly moderates the relationship of workplace innovation and employee performance in the context of employees working at different corporate sectors of employees. LimitationsThe study has limitation in the form of unavailability of the qualitative evidence. Moreover, the employees from diversified sectors were approached despite concentrating on the employees of a single sector thereby adding complexity in comprehending on what particular sectors the phenomenon can be applied.